The senior citizens loyalty and services satisfaction on the use of their IDs in purchasing consumer products - Orias, Kimberlyn G.; Sanchez, Marita G. (Elsevier Ltd., 2014)
In this study, the loyalty and satisfaction of senior citizens was investigated to determine the criteria on their being loyal to the businesses that offer better satisfaction.Correlating the loyalty and services satisfaction they received from buying goods and services, pointed out the potential challenges for businesses to improve advertising and sales promotions in media.Consequently, the senior citizens who enjoy their second citizenship understand the circumstances of being elderly citizens as they reach the age of 60 years old.The many benefits they receive from monthly pensions are satisfaction from being senior citizens.The business owners, and other institutions are likewise delighted from the criteria these elderly judged as “loyalty indicators” for their business expansion.